An inkjet‐printed sulfonephthalein dye indicator array for volatile amine detection. Issue 2 (24th January 2020) - Luo, Xiaoyu; Lim, Loong‐Tak
Abstract : Abstract: Colorimetric indicators are versatile for applications such as intelligent food packaging, for reflecting the actual quality and/or monitoring distribution history of food products. In this study, a colorimetric indicator array composed of sulfonephthalein dyes was successfully developed by piezoelectric inkjet printing, for the detection of volatile amines—the primary spoilage gases for fish and seafood products. The printing inks were formulated in water/ethanol/1‐butanol mixture. By refilling the printer's cartridges with our formulated inks and controlling the red, green, and blue color parameters, a 7 × 9 indicator array was printed onto inkjet transparency films. The color response of the indicator array was tested with different volatile amines at various concentrations. The array indicator was capable of discriminating six different volatile amines: ammonia, trimethylamine, dimethylamine, triethylamine, piperidine, and hydrazine. The printability of the inks was investigated by characterizing their density, surface tension, and dynamic viscosity, dictating that all formulated inks were printable fluid. The microstructural morphologies of the printed dyes on transparency films were evaluated using scanning electron microscopy. Interactions of the dye with the volatiles were studied by Fourier transform infrared spectroscopy. In summary, the piezoelectric inkjet printing method presented in this study offers a convenient, efficient, and flexible means to fabricate colorimetric indicators for detecting food spoilage volatiles. These indicators are promising as sensing components in intelligent packaging systems, to reveal the freshness of fish products by correlating with quality parameters such as total volatile basic nitrogen, microbial growth, and sensory attributes. Further studies on the feasibility of using the array indicators in real food packaging systems, development of strategy to mitigate the potential migration of the indicator dyes, and designing array patterns optimal for machine/human interpretation, are important to commercialize the technology. Practical Application: Piezoelectric inkjet printing offers a convenient way to fabricate sensing materials and aligns with industrial packaging operations. The use of indicators on food package helps consumers more accurately perceive real‐time food quality information.